Improving student diet and food security in higher education using participatory and co-creation approaches: a systematic review - Tamar Assilian; Henri Dehove; Hélène Charreire; Julia Baudry; Emmanuelle Kesse-Guyot; Sandrine Péneau; Chantal Julia; Olivia Gross; Jean-Michel Oppert; Alice Bellicha (BMC, 2024)
Abstract Background Higher education students are an important target group for public health nutrition interventions. When designing tailored and contextually relevant interventions, participatory and co-creation approaches are increasingly recognized as promising but their use and effectiveness has not been assessed in this type of population. We systematically reviewed interventions aiming to improve dietary quality and/or food security in higher education settings with the aims 1) to identify and describe their participatory and co-creation approaches and 2) to compare the effectiveness of interventions using or not using participatory and co-creation approaches. Methods Our search in PubMed, Google Scholar, Web of Science, EMBASE was performed in January 2023 and yielded 3658 unique records, out of which 42 articles (66 interventions) were included. Effectiveness of interventions was assessed at the individual level (longitudinal evaluations) or at the group level (repeated cross-sectional evaluations). A five-level classification was used to describe a continuum of engagement from students and other partners in the intervention design and implementation: no participation (level one), consultation, co-production, co-design and co-creation (levels two to five). To synthetize effectiveness, comparisons were made between studies without participation (level one) or with participation (levels two-five). Results Ten (24%) out of 42 studies used a participatory and co-creation approach (levels two-five). Studies using a participatory and co-creation approach reported a positive finding on individual-level outcome (i.e. overall diet quality or food group intake or food security) in 5/13 (38%) intervention arms (vs 13/31 or 42% for those without participation). Studies using a participatory and co-creation approach reported a positive finding on group-level outcomes (i.e. food choices in campus food outlets) in 4/7 (57%) (vs 8/23 or 35% in those without participation). Conclusions Participatory and co-creation approaches may improve the effectiveness of nutrition interventions in higher education settings but the level of evidence remains very limited. More research is warranted to identify best co-creation practices when designing, implementing and evaluating nutritional interventions in the higher education setting. Trial registration PROSPERO registration number CRD42023393004.